Postharvest quality of 'Cripps Pink' apple fruit influenced by ethylene antagonists during controlled atmosphere storage with photocatalytic oxidation. (14th February 2022) - Tokala, Vijay Yadav; Singh, Zora; Kyaw, Poe Nandar
Abstract: BACKGROUND: The present study investigated the efficacy of 1 H ‐cyclopropa[ b ]naphthalene (NC) and 1 H ‐cyclopropabenzene (BC) with respect to antagonizing ethylene action and maintaining postharvest fruit quality in 'Cripps Pink' apple stored in a controlled atmosphere comprising 3.45 ± 0.45% oxygen and 2.40 ± 0.36% carbon dioxide with photocatalytic oxidation (PCO) at 0 ± 1 °C and 90 ± 5% relative humidity. RESULTS: The BC, NC, and 1‐methylcyclopropene (1‐MCP) fumigation treatments delayed the climacteric peaks onset and retarded ethylene production rates compared to control fruit. Treatments with ethylene antagonist also maintained fruit firmness (up to 1.12 times), titratable acidity (up to 1.08 times), malic acid (up to 1.23 times), ascorbic acid (up to 1.12 times) and total phenol levels (up to 1.19 times) higher compared to that in control fruit. The 1‐MCP was more efficient in reducing the rates of ethylene production compared to NC and BC, but, in the case of all other fruit quality parameters investigated, the effect of NC and BC treatments were on a par with 1‐MCP. CONCLUSION: The NC and BC have the potential to be used as ethylene antagonists in 'Cripps Pink' apple fruit stored in a controlled atmosphere with PCO. The efficacy of different concentrations of NC and BC in downregulating ethylene action, as well as interactive effects of PCO on the performance of ethylene antagonists, still warrants further investigation. © 2022 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.